The Effect Of Twin Cards Media On Students’ Speaking Ability In Grade VIII Of Junior High School Hosanna Medan - Lastri Wahyuni Manurung; Nurhayati Sitorus; Robeca Shanty Sitohang; Carolina Pakpahan (Journal on Education, 2023)
Speaking is one of the English skills that must be mastered by English learners. There are many ways to hone students' speaking skills in class VIII students of SMP Hosanna Medan for the 2022/2023 academic year. One way is to use Twin Cards media. This research aims to find out whether the twin card media affects the students' ability in speaking English, especially in class VIII SMP Hosanna Medan. Researcher used true experimental quantitative research, where researcher used two classes to study, namely the experimental class and the control class. The use of twin card media is only given to the experimental class, and the control class is taught without any method or treatment. From these research studies, researchers can find differences between the experimental class and the control class. It is known from the average value of the data presented that has been calculated in SPSS version 26 that the value of the experimental class increased from 50.62 in the pre-test to 75.23 in the post-test because after being given the treatment. Meanwhile, the pretest in the control class was 45.83 and the posttest score was 53.58 because the researchers did not treat it. The t value obtained from the post-test results between the experimental class and the control class is 6, 8248627972. This shows that the results of the t-score > t table (2,064) and the sig. (2 tailed) is 0.000 < 0,005. From the data presented, it can be concluded that there is an effect of using twin cards media on students' speaking abilities in class VIII students of SMP Hosanna Medan in the 2022/2023 Academic Year.